MicroRNA's – The vibrant performers in the oral cancer scenario. Issue 1 (November 2020) - Solomon, Monica Charlotte; Radhakrishnan, Raghu Anekal
Summary: MicroRNAs (miRNAs) are a family of small non-coding (18–22 nucleotide) RNA molecules. These molecules regulate gene expression by either inhibiting mRNA translation or by degrading mRNA. A single miRNA can control the expression of target genes, and the expression of a target gene can be regulated by multiple miRNAs. They are key regulators of various biological and pathological processes. These include cell proliferation, development and tumorigenesis. Novel studies have discovered definite signature miRNAs in the initiation and progression of cancers. Interestingly, miRNAs have also been found in fragile genomic sites that are associated with increased cancer risk. These micro RNAs regulate the expression of several genes that play a crucial role in the transition of normal oral mucosa through dysplasia to malignancy. The aim of this review is to recapitulate the current understanding of the many miRNAs that have been identified, the genes that they target and the role that they play in the carcinogenic pathway. The review also highlights the prospective role of miRNAs in the diagnosis, prognosis and treatment of oral cancers.